DNA methylation and expression of Homeobox gene family as diagnostic and prognostic markers in human hepatocellular carcinoma - Sumadi Lukman Anwar; Ulrich Lehmann (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTHomeobox genes consist of a family of evolutionarily conserved genes that play important roles in morphogenesis, embryogenesis, and cell fate determination. Re-expression of embryogenic genes has been associated with carcinogenesis of human cancers. Aberrant expression of homeobox genes has been increasingly found to modulate diverse processes such as cell proliferation, cell death, metastasis, angiogenesis and DNA repair. We studied DNA methylation and expression of homeobox gene family in human hepatocellular carcinoma (HCC), the fifth most common cancer and the third leading cause of cancer mortality worldwide. We performed microarray for comprehensive DNA methylation and gene expression using primary HCC samples and healthy liver tissues. Confirmation using pyrosequencing and RT-PCR was then performed. Clustering both unsupervised and supervised methods using Qlucore software was then performed. Enrichment of homeobox genes both for DNA methylation and gene expression could differentiate HCC and the healthy liver tissues. Profile of homeobox gene methylation could further predict clinical outcome. Inverse correlation between DNA methylation and gene expression was shown (HOXA9, Spearman r=-0.49, p=0.002). Gain of DNA methylation in HOXA9, HOXA13, and MEOX1 correlated with shorter HCC survival (log-rank Mantel-Cox test p=0.02, with median survival 50 and 490 weeks, respectively). We demonstrated potential roles of DNA methylation and gene expression profiles of Homeobox gene family as diagnostic and prognostic marker in patients with HCC.